T cell numbers correlate with neuronal loss rather than with seizure activity in medial temporal lobe epilepsy. (6th May 2021) - Tröscher, Anna R.; Sakaraki, Eirini; Mair, Katharina M.; Köck, Ulrike; Racz, Attila; Borger, Valeri; Cloppenborg, Thomas; Becker, Albert J.; Bien, Christian G.; Bauer, Jan
Abstract: Objective: Medial temporal lobe epilepsy (MTLE) is a drug‐resistant focal epilepsy that can be caused by a broad spectrum of different inciting events, including tumors, febrile seizures, and viral infections. In human epilepsy surgical resections as well as in animal models, an involvement of the adaptive immune system was observed. We here analyzed the presence of T cells in various subgroups of MTLE. We aimed to answer the question of how much inflammation was present and whether the presence of T cells was associated with seizures or associated with hippocampal neurodegeneration. Methods: We quantified the numbers of CD3 + T cells and CD8 + cytotoxic T cells in the hippocampus of patients with gangliogliomas (GGs; intrahippocampal and extrahippocampal, with and without sclerosis), febrile seizures, and postinfectious encephalitic epilepsy and compared this with Rasmussen encephalitis, Alzheimer disease, and normal controls. Results: We could show that T cell numbers were significantly elevated in MTLE compared to healthy controls. CD3 + as well as CD8 + T cell numbers, however, varied highly among MTLE subgroups. By comparing GG patients with and without hippocampal sclerosis (HS), we were able to show that T‐cell numbers were increased in extrahippocampal GG patients with hippocampal neuronal loss and HS, whereas extrahippocampal GG cases without hippocampal neuronal loss (i.e., absence of HS) did not differ from healthy controls. Importantly, T cell numbers in MTLE correlated with the degree of neuronal loss, whereas no correlation with seizure frequency or disease duration was found. Finally, we found that in nearly all MTLE groups, T cell numbers remained elevated even years after the inciting event. Significance: We here provide a detailed histopathological investigation of the involvement of T cells in various subgroups of MTLE, which suggests that T cell influx correlates to neuronal loss rather than seizure activity.